Prevention Technology for Strong Mine Pressure Disaster in the Hard-Roof Large-Mining-Height Working Face - Hongfei Duan; Lijuan Zhao (Shock and Vibration)
The movement and destruction of the hard roof in a stope is an important reason for the occurrence of strong ground pressure disasters at the working face. Considering Tongxin Coal Mine as the engineering background, the stress distribution law of the surrounding rock and the overburden rock damage characteristics of a large-mining-height working face under the hard roof were investigated. To solve the problem whereby the stope’s hard roof is difficult to collapse, the hard rock key stratum of the roof was hydraulically fractured to weaken the mechanical properties of the roof rock stratum. Additionally, microseismic monitoring technology was used to monitor the cracking effect of the rock stratum. The theoretical calculation and numerical simulation results reveal that, after hydraulic fracturing, a crack with a more consistent trend formed inside the hard rock stratum and a large area of the rock stratum was damaged. According to the monitoring results of the stope stress after hydraulic fracturing, the law governing the occurrence of the leading bearing pressure was in effect. In contrast, the influence range and peak strength of the leading bearing pressure were considerably reduced at the working face after hydraulic fracturing. After performing hydraulic fracturing on the roof of the working face, the bearing pressure of the working face can satisfy the production requirements better. Finally, the results obtained through this study can be used as a reference for determining the width of coal pillars under similar mining conditions.